Citicoline in Acute Ischemic Stroke: Case Report - Rimbun, Surjadi; Anto, Endy Juli (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Stroke is the third most common disease after heart disease and cancer and a leading cause of disability worldwide. The most common type of stroke is non-hemorrhagic stroke (SNH) or Acute Ischemic Stroke, which accounts for about 85-87% of all cases. The purpose of this case report is to examine the benefits of citicoline in a patient with SNH. Case Presentation: In this case, a 63-year-old man was admitted to the Emergency Room of the Agung Mulia Inpatient Clinic on February 25, 2023 with complaints of inability to move his right arm and leg since 5 days before entering the clinic. The complaint was felt suddenly when the patient woke up in the morning. The patient also complained of weakness and difficulty speaking and slurred speech accompanied by difficulty swallowing. The voice could still speak but was unclear but the patient understood what was being said to him. Other complaints such as headaches, nausea, vomiting, bowel and urination disorders, and fainting were denied by the patient. The patient was treated at a hospital near his house on February 21, 2023 and underwent a CT scan of the head and was treated as an outpatient. The results of the CT scan on February 21, 2023, axial section of the head without intravenous contrast, obtained the following results: Infraterritorial cerebellum and 4th ventricle appear normal, Supreterritorial hypodense lesions appear on the left lateral periventricular and in the left parietal, No midline shift, Cortical sulci and prominent ventricular system. It was concluded that the left lateral periventricular and left parietal cerebral infarction were in accordance with Non-Hemorrhagic Stroke (SNH). Senile cerebral atrophy. Based on anamnesis, physical examination, and supporting examinations. The clinical diagnosis in this case was right hemiparesis and paresis of nerves VII, IX, and X, et causa non-hemorrhagic stroke (SNH) with electrolyte disorders (Electrolyte Imbalance), given general and specific management. Results: For general management that can be given is semi-fowler position, oxygen administration, administration of antihypertensive drugs and maintaining fluid and nutritional intake. While specific management with pharmacology by administering citicoline and clopidogrel is given to this patient. Conclusion: Citicoline works to prevent brain damage (neuroprotection) and helps the formation of cell membranes in the brain (neurorepair). The benefits of citicoline in this patient are seen in motor and neurological improvements based on NIHSS assessments.